Perbedaan Efektifitas Pijat Oksitosin Manual Dan Non Manual (Stipro) Terhadap Percepatan Pengeluaran ASI Pada Ibu Postpartum Di RSUD Dr. Saiful Anwar Malang Jawa Timur - Dina Agustin Tri Kusumaning Rahayu; Yuniar Angelia Puspadewi; Waifti Amalia (Media Husada Journal of Midwifery Science, 2026)
Abstract Infant mortality rates can be significantly reduced if newborns receive breast milk immediately. Breastfeeding within the first hour—supported by programs such as Early Initiation of Breastfeeding (IMD) and exclusive breastfeeding—can save millions of newborn lives. However, many postpartum mothers experience difficulties with breast milk expression. Oxytocin massage is one solution to address issues with the flow of breast milk. Using an oxytocin massage device (STIPRO) can further assist postpartum mothers with milk expression. This study aimed to determine the difference in effectiveness between manual oxytocin massage and non-manual massage (using the STIPRO device) regarding the speed of breast milk expression among postpartum mothers at Dr. Saiful Anwar Regional General Hospital (RSUD) in Malang, East Java. A pre-experimental design with a post-test-only control group was employed. Purposive sampling was used to select 30 participants: 15 respondents received manual oxytocin massage, and 15 received non-manual massage (STIPRO). Research instruments included the STIPRO device and an observation checklist for breast milk expression. The t-test results showed a p-value of 0.000 (less than a = 0.05) and a calculated t-value (5.551) greater than the t-table value (2.048), indicating a significant difference in effectiveness between manual and non-manual (STIPRO) oxytocin massage regarding the speed of breast milk expression. The average volume of expressed breast milk in the non-manual massage group (intervention group) was 17.6 cc, which was higher than that of the manual massage group (control group) at 5.0 cc. It is concluded that there is a difference in effectiveness between manual and non-manual (STIPRO) oxytocin massage; breast milk expression was higher in the intervention group than in the control group. Respondents are encouraged to practice non-manual oxytocin massage (STIPRO) and proper breast care at home to ensure continued milk production and smooth expression.